Western Balkans : Increasing Women's Role in the Economy - Atoyan, Ruben (IMF Working Papers; Working Paper ;, 2017)
The Western Balkan countries have some of the lowest female labor force participation and employment rates across Europe. Almost two-thirds of working age women in the region are either inactive or unemployed: a huge bite into human capital for a region that endures high emigration and faces declining working age population. The paper uses both macro- and micro-level data to explore what explains low participation and employment rates among women in the region. Our findings show that improving educational attainment, having a more balanced family leave policy, and reducing tax wedge help improve participation of women in the labor force. However, these measures are not enough to notably improve employability of women, which require stronger growth supported by robust institutions.